Complex geomorphologic assemblage of terrains in association with the banded terrain in Hellas basin, Mars. (February 2016) - Diot, X.; El-Maarry, M.R.; Schlunegger, F.; Norton, K.P.; Thomas, N.; Grindrod, P.M.; Chojnacki, M.
Abstract: Hellas basin acts as a major sink for the southern highlands of Mars and is likely to have recorded several episodes of sedimentation and erosion. The north-western part of the basin displays a potentially unique Amazonian landscape domain in the deepest part of Hellas, called "banded terrain", which is a deposit characterized by an alternation of narrow band shapes and inter-bands displaying a sinuous and relatively smooth surface texture suggesting a viscous flow origin. Here we use high-resolution (HiRISE and CTX) images to assess the geomorphological interaction of the banded terrain with the surrounding geomorphologic domains in the NW interior of Hellas to gain a better understanding of the geological evolution of the region as a whole. Our analysis reveals that the banded terrain is associated with six geomorphologic domains: a central plateau named Alpheus Colles, plain deposits (P1 and P2), reticulate (RT1 and RT2) and honeycomb terrains. Based on the analysis of the geomorphology of these domains and their cross-cutting relationships, we show that no widespread deposition post-dates the formation of the banded terrain, which implies that this domain is the youngest and latest deposit of the interior of Hellas. Therefore, the level of geologic activity in the NW Hellas during the Amazonian appears to have been relatively low and restricted to modification of the landscape through mechanical weathering, aeolian and periglacial processes. Thermophysical data and cross-cutting relationships support hypotheses of modification of the honeycomb terrain via vertical rise of diapirs such as ice diapirism, and the formation of the plain deposits through deposition and remobilization of an ice-rich mantle deposit. Finally, the observed gradual transition between honeycomb and banded terrain suggests that the banded terrain may have covered a larger area of the NW interior of Hellas in the past than previously thought. This has implications on the understanding of the evolution of the deepest part of Hellas. Highlights: Hellas basin's NW interior displays a complex assemblage of terrains. The banded terrain may be the youngest widespread domain of Hellas. The banded terrain may have covered a large part of the NW interior of Hellas. The geologic activity seems to have significantly dwindled in the Amazonian.